Associations between depression and different measures of obesity (BMI, WC, WHtR, WHR) - Wiltink, Jörg (BioMed Central, 2013)
BACKGROUND: Growing evidence suggests that abdominal obesity is a more important risk factor for the prognosis of cardiovascular and metabolic diseases than BMI. Somatic-affective symptoms of depression have also been linked to cardiovascular risk. The relationship between obesity and depression, however, has remained contradictory. Our aim was therefore to relate body mass index (BMI) and different measures for abdominal obesity (waist circumference, WC, waist-to-hip ratio, WHR, waist-to-height ratio, WHtR) to somatic vs. cognitive-affective symptoms of depression. METHODS: In a cross-sectional population based study, data on the first N = 5000 participants enrolled in the Gutenberg Health Study (GHS) are reported. To analyze the relationship between depression and obesity, we computed linear regression models with the anthropometric measure (BMI, WC, WHR, WHtR) as the dependent variable and life style factors, cardiovascular risk factors and psychotropic medications as potential confounders of obesity/depression. RESULTS: We found that only the somatic, but not the cognitive-affective symptoms of depression are consistently positively associated with anthropometric measures of obesity. CONCLUSIONS: We could demonstrate that the somatic-affective symptoms of depression rather than the cognitive-affective symptoms are strongly related to anthropometric measures. This is also true for younger obese starting at the age of 35 years. Our results are in line with previous studies indicating that visceral adipose tissue plays a key role in the relationship between obesity, depression and cardiovascular disease.